Pastoral Care in English Schools: A Canadian Perspective - Lang, Peter; Young, Richard A. (Canadian Journal of Counselling and Psychotherapy, 2011)
In this paper, pastoral care, the welfare dimension of English secondary schools, is examined in light of North American school counselling and guidance practices. Although not precisely defined, pastoral care has prospered in recent years. At the same time, school counselling has not found wide acceptance. The specific social, historical, and cultural milieu is one source for understanding this development. The discipline/control emphasis of pastoral care does not correspond to North American practices in guidance and counselling. However, some commonalities in the academic/curricular and pastoral/welfare components are noted. At present, pastoral care programs are implemented through non-specialized teachers while North American practices depend on the specialized counsellor.